Constructing CdSe QDs modified porous g-C3N4 heterostructures for visible light photocatalytic hydrogen production. (30th December 2021) - Zhang, Zheng; Kang, Yuyang; Yin, Li-Chang; Niu, Ping; Zhen, Chao; Chen, Runze; Kang, Xiangdong; Wu, Fayu; Liu, Gang
Highlights: The CdSe/PCN heterostructure is constructed with homogeneous distribution of CdSe QDs throughout PCN matrix. The existence of CdSe QDs enhances the visible light absorption of the PCN. The CdSe/PCN heterostructure effectively facilitates the separation of photo-carriers by shortening photo-carrier transfer distance in the bulk. The CdSe/PCN heterostructure exhibits much higher photocatalytic hydrogen production activities than CdSe and PCN. Abstract: Constructing heterostructures with narrow-band-gap semiconductors is a promising strategy to extend light absorption range of graphitic carbon nitride (g-C3 N4 ) and simultaneously promote charge separation for its photocatalytic activity improvement. However, its highly localized electronic states of g-C3 N4 hinder photo-carrier migration through bulk towards heterostructure interfaces, resulting in low charge carrier separation efficiency of solid bulk g-C3 N4 -based heterostructures. Herein, porous g-C3 N4 (PCN) material with greatly shortened migration distance of photo-carriers from bulk to surface was used as an effective substrate to host CdSe quantum dots to construct type II heterostructure of CdSe/PCN for photocatalytic hydrogen production. The homogeneous modification of the CdSe quantum dots throughout the whole bulk of PCN together with proper band alignments between CdSe and PCN enables the effective separation of photo-generated charge carriers in the heterostructure. Consequently, the CdSe/PCN heterostructure photocatalyst gives the greatly enhanced photocatalytic hydrogen production activity of 192.3 μmol h −1, which is 4.4 and 8.1 times that of CdSe and PCN, respectively. This work provides a feasible strategy to construct carbon nitride-based heterostructure photocatalysts for boosting visible light driven water splitting performance. Graphical abstract: Image, graphical abstract